Polar Remote Sensing - Volume II: Ice Sheets - Robert Massom; Lubin, D (2006)
Polar Remote Sensing is a two-volume work providing a comprehensive, multidisciplinary discussion of the applications of satellite sensing. Volume 2 focuses on the ice sheets, icebergs, and interactions between ice sheets and the atmosphere and ocean. It contains information about the applications of satellite remote sensing in all relevant polar related disciplines, including glaciology, meteorology, climate and radiation balance and oceanography. It also provides a brief review of the state-of-the-art of each discipline, including current issues and questions. Various passive and active remote sensor types are discussed, and the book then concentrates on specific geophysical applications. Its interdisciplinary approach means that major advances and publications are highlighted.